Increased antitumor efficacy of PD-1-deficient melanoma-specific human lymphocytes - Nathalie Labarrière; Lucine Marotte; Sylvain Simon; Virginie Vignard; Emilie Dupre; Malika Gantier; Jonathan Cruard; Jean-Baptiste Alberge; Melanie Hussong; Cecile Deleine; Jean-Marie Heslan; Jonathan Shaffer; et al. (Journal for ImmunoTherapy of Cancer, 2020)
Background Genome editing offers unique perspectives for optimizing the functional properties of T cells for adoptive cell transfer purposes. So far, PDCD1 editing has been successfully tested mainly in chimeric antigen receptor T (CAR-T) cells and human primary T cells. Nonetheless, for patients with solid tumors, the adoptive transfer of effector memory T cells specific for tumor antigens remains a relevant option, and the use of high avidity T cells deficient for programmed cell death-1 (PD-1) expression is susceptible to improve the therapeutic benefit of these treatments.Methods Here we used the transfection of CAS9/sgRNA ribonucleoproteic complexes to edit PDCD1 gene in human effector memory CD8+ T cells specific for the melanoma antigen Melan-A. We cloned edited T cell populations and validated PDCD1 editing through sequencing and cytometry in each T cell clone, together with T-cell receptor (TCR) chain’s sequencing. We also performed whole transcriptomic analyses on wild-type (WT) and edited T cell clones. Finally, we documented in vitro and in vivo through adoptive transfer in NOD scid gamma (NSG) mice, the antitumor properties of WT and PD-1KO T cell clones, expressing the same TCR.Results Here we demonstrated the feasibility to edit PDCD1 gene in human effector memory melanoma-specific T lymphocytes. We showed that PD-1 expression was dramatically reduced or totally absent on PDCD1-edited T cell clones. Extensive characterization of a panel of T cell clones expressing the same TCR and exhibiting similar functional avidity demonstrated superior antitumor reactivity against a PD-L1 expressing melanoma cell line. Transcriptomic analysis revealed a downregulation of genes involved in proliferation and DNA replication in PD-1-deficient T cell clones, whereas genes involved in metabolism and cell signaling were upregulated. Finally, we documented the superior ability of PD-1-deficient T cells to significantly delay the growth of a PD-L1 expressing human melanoma tumor in an NSG mouse model.Conclusion The use of such lymphocytes for adoptive cell transfer purposes, associated with other approaches modulating the tumor microenvironment, would be a promising alternative to improve immunotherapy efficacy in solid tumors.